PENGARUH PROFITABILITAS DAN AKTIVITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN RETAIL - Lestari, Nurdika Dewi; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is aimed to test whether profitability which consists of return on assets, return on equity, net profit margin, operating profit margin and activity which consists of inventory turnover affect to the profit growth of retail companies which are listed in Indonesia Stock Exchange in 2012-2014 periods. This research has been done by using quantitative approach and multiple regressions analysis method. The data has been done by using secondary data from publication statement from official website www.idx.co.id and IDX Corner STIESIA Surabaya. The data collection technique has been carried out by using documentation and literature study. The sample collection has been done by performing purposive sampling. 17 companies which have met the criteria have been selected as samples, so the numbers of observation are 51 observations. The result of this research shows that: (1) return on assets has positive influence to the profit growth; (2) return on equity has positive influence to the profit growth; (3) net profit margin has positive influence to the profit growth; (4) operating profit margin has positive influence to the profit growth; and (5) inventory turnover has positive influence to the profit growth.Keywords: Profitability ratio, activity ratio, profit growth.